To Carry or not to Carry: Predictors of Support for Allowing Probation/Parole Officers to Carry Firearms. Issue 2 (3rd April 2018) - Rhineberger-Dunn, Gayle; Mack, Kristin Y.
ABSTRACT: The purpose of this article is to explore predictors of community corrections staff's opinions on allowing probation/parole officers to carry firearms on the job. Using a sample of nearly 300 probation/parole and residential officers, the authors analyze the role of demographic factors, job characteristics (e.g., job tenure), and workplace perceptions (e.g., dangerousness, threat of harm) in determining opinions on this issue. Findings indicate that predictors of support for firearms carrying among probation/parole officers differ by gender and tenure, as well as by perceptions of job dangerousness and role orientation.